Moral Messaging: Testing a Framing Technique during a Pandemic. Issue 1 (2nd January 2023) - Misiak, Michal; Curry, Oliver Scott; Tureček, Petr
Abstract: We experimentally investigated whether appeals to moral principles—as operationalized by the theory of Morality-as-Cooperation—increase pandemic-related public health behavior. Participants (from the USA and India) were presented with persuasive messages, asked about their intentions to follow pandemic-related restrictions, were asked to donate to a charity fighting COVID-19, and completed the Morality-as-Cooperation Questionnaire. We found that moral messages were more effective than non-moral messages in increasing Prosocial Intentions and Donations, especially messages appealing to Heroism. In the US sample, the effect of moral messages was larger when they were concordant with participants' moral values. We also found that some moral messages were effective only in a particular population. This paper outlines the necessary next steps for using Morality-as-Cooperation for evidence-based communication.